Numerical Simulation of the Collision of a Droplet with a Heated Solid Surface - Gumulya, Monica; Utikar, Ranjeet; Pareek, Vishnu; Tade, Moses; Evans, G. (CSIRO, 2012)
This paper discusses the development of a model for the evaporation of a droplet on heated solid surface. Associated issues include the construction of evaporative source terms, and their implementation into a multiphase (VOF) framework. This was done in conjunction with the Level Set method (CLSVOF), allowing the evaporation at the liquid-vapour and liquid-solid interface to be characterised accurately. The validity of the model was examined through comparisons with published experimental data. The model was found to be capable of reproducing the reduced droplet spreading rate as the surface temperature is increased away from the saturation temperature. This decrease in surface wetting results from the combined effects of surface tension, viscous forces and contact line evaporation. The effects of increased pressure due to evaporation, which in some cases can be quite severe such that the liquid gets lifted-off from the surface, were also captured, in good agreement with experimental observations.